(untitled) (Anclajes, 2014)
As a means to counter the historical balkanization of the Antilles, the essay writing of Édouard Glissant, as well as that of Cuban Antonio Benítez Rojo and Barbadian Kamau Brathwaite, elaborates an imaginary integration of the Caribbean, promoting cultural linkages. By looking into similar concepts and metaphors displayed in their essays, we distinguish common interests (“lieux-communs”, according to Glissant’s Philosophie de la relation (2009)) as well as the voluntary affiliation of the authors with one another by means of a mutual appropriation of ideas and various intertextual relations. Although the authors belong to different linguistic regions, the translation of their works and the contacts established among them have favored the construction of a “repeating essay”: a (common) Caribbean discourse. In particular, I focus on the continuities that the essays establish with the Caribbean anti-colonialist tradition and the collectivist revolutionary spirit of the 60s and 70s, beyond the “postmodern perspective” the authors may claim to assume. Keywords: essay; Caribbean; Antonio Benítez Rojo; Édouard Glissant; Kamau Brathwaite